Legal Protection for Investors in Equity Crowdfunding Practices on the Bizhare Application - Angga Putra Adi Pratama; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
This research discusses legal protection for investors in the practice of crowdfunding through the equity crowdfunding model conducted through the Bizhare application. Equity crowdfunding has become a popular method to raise funds from individual investors in the form of shares or ownership in startup companies. However, this practice also involves significant risks for investors, including the risk of loss of investment and the risk of misuse of funds by irresponsible parties. Therefore, legal protection for investors is essential to ensure safety and fairness in the practice of crowdfunding through the Bizhare app. This study involves an analysis of the applicable legal framework related to crowdfunding and investor protection in the relevant countries. In addition, the research methods used include comparative legal analysis as well as a review of crowdfunding practices on the Bizhare app. This research aims to identify the weaknesses and strengths of existing regulations, and provide recommendations for improvements that can strengthen legal protection for investors. As such, this research is expected to provide a better understanding of how the law can play an effective role in protecting investors in crowdfunding practices, so as to promote trust and wider participation in the equity crowdfunding ecosystem. The results of this study provide an in‐depth understanding of the legal framework required to protect investors in crowdfunding practices through the Bizhare app.